A study of pattern of psychogenic morbidity and associated biosocial factors in school going adolescent girls - Lamba, Ratandeep; Kumar, Sanjeev; Rana, Ravi (International Journal Of Community Medicine And Public Health, 2016)
Background: Psychiatric & psychogenic problems in children in India are rising and reported-cases represent only the tip of the iceberg, large number remains unreported. During adolescence, children need special care as they undergo a complex process of emotional, physical and social changes. At times, failure to adjust with these changes leads to mental health problems. Both, girls and boys are susceptible to suffer from these problems but, for adolescent girls, the problem gets compounded due to multitude social factors. Adolescents are the future citizens of a country and it is imperative to systematically address their needs. The present study was planned to study psychosocial problems in school going adolescent girls & biosocial factors related to it. Methods: The study population comprised of the adolescent girls attending Queen Victoria, Girls Inter College located in the heart of Agra city. 880 school girls of age group 10-19 years whose parents or guardians gave written voluntary consent participated in the study, comprised the study population. To identify psychogenic morbidity Youth Self-report & M. I. N. I. International neuropsychiatric interview were used. Socio-demographic details of the girls were collected on a socio-demographic data sheet prepared for this study & conclusions were drawn. Results: Psychogenic morbidities were found in 13.5% (119/880) of the school going adolescent girls (10-19 years). Highest psychiatric illnesses were in those who were 17 (20.4%) followed by 16 (15.2%) & 15 (14%) years of age respectively. Conclusions: According to ICD 10 criteria, 34 (28.6%) of the girls belonged to neurotic stress related & somatoform disorders wherein anxiety disorders (generalised anxiety disorder, phobias & OCD) were the most common. 29 (24.3%) of the girls had mood & affective disorders.